Searching for strong institutions in Jalisco, Mexico, for sustainable development with access to justice - García-González, Javier Alberto (DIXI, 2026)
This paper is based on the premise that, despite the advances and progress made in Mexico in terms of access to justice, there is data that shows a worrying trend both in terms of the quantification and recording of results, as is the case globally, and in terms of the quality of the data presented by the various agencies at the national, state, and municipal levels, specifically in the case of the state of Jalisco. This paper is based on the classification of policies implemented according to Francisco Garrido Peña, since the nature of these policies gives rise to different information in the reports and plans presented. Despite the existence of guidelines and methodologies, the development policies adopted by each agency end up obeying different intentions and conceptual frameworks, which leads to a lack of homogeneity.